1980
DOI: 10.1136/gut.21.12.1041
|View full text |Cite
|
Sign up to set email alerts
|

Cell kinetics in the jejunal crypt epithelium in malabsorption syndrome with cow's milk protein intolerance and in coeliac disease of childhood.

Abstract: (CMI) and 12 of these on a cow's milk free diet were compared with 47 children with untreated coeliac disease, with 15 of these on a gluten free diet, and with 15 controls. The total number of cells in the crypts of the patients with CMI was 1 8 times (p<0.001) and in patients with coeliac disease 2-4 times (P < 0.001) that seen in the controls. During the elimination diet the total number of cells in the crypts returned to the level seen in the controls. The mitotic indices, both crude and corrected, were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

1982
1982
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 15 publications
0
17
1
Order By: Relevance
“…Thus, villus/crypt-ratio (CD: 0.2 • 0.1, CMPI: 0.8 • 0.9) and crypt depth (CD: 360• CMPI: 217• p<0.015) were shown to be statistically different in CD and CMPI of equal biopsy grading. In CMPI, crypt hyperplasia appeared to be less prominent than in CD, although it cannot be decided from our data if this difference is merely age-dependent, or if it reflects some pathogenetic difference in morphogenesis and cell kinetic changes occuring in CD and CMPI, as has been suggested recently [11,14,40]. In contrast to previous studies [34], there was no morphometric difference found between CD on a gluten-free diet and controls.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Thus, villus/crypt-ratio (CD: 0.2 • 0.1, CMPI: 0.8 • 0.9) and crypt depth (CD: 360• CMPI: 217• p<0.015) were shown to be statistically different in CD and CMPI of equal biopsy grading. In CMPI, crypt hyperplasia appeared to be less prominent than in CD, although it cannot be decided from our data if this difference is merely age-dependent, or if it reflects some pathogenetic difference in morphogenesis and cell kinetic changes occuring in CD and CMPI, as has been suggested recently [11,14,40]. In contrast to previous studies [34], there was no morphometric difference found between CD on a gluten-free diet and controls.…”
Section: Discussioncontrasting
confidence: 84%
“…Differences between IEL counts in CD (793+173) and CMPI (320___143) were statistically highly significant Co < 0.001), even when only biopsies of equal enteropathy grading were analysed. IEL data in CMPI have been inconsistently reported [14,30]. This might be due to different grades of the enteropathies in patient and control groups which have been taken into account by this study.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Using light microscopy it is possible to see that the surface epithelial cells in biopsy specimens of patients with untreated CD are flattened, their cytoplasm shows vacuolization and the brush border and basement membrane are damaged (6). Similar increase in cell kinetics is, however, observed in other types of disease with crypt hyperplastic villous atrophy, such as in severe cow's milk allergy (9). In crypt epithelial cells, the frequency of mitoses is increased.…”
Section: General Morphology Of the Jejunal Mucosa In CDmentioning
confidence: 87%